數位原住民學習風格及其對適性課程與教學之啟示 The Learning Styles of Digital Natives and the Implication for Adaptive Instruction - 陳信助 Hsin-Tzu (Tommy) Chen; 侯雅雯 Ya-Wen Hou (Journal of Curriculum Studies, 2021)
「以學生為中心且適性的教與學」已是現今數位時代中刻不容緩的事。為推動 適性課程與教學，首要步驟可謂是了解學生的學習風格。爰此，本研究旨在了解今日數位原住民大學生學習風格之分布狀態及強度，並為適性教學提出一些建議。本研究以臺北市某私立大學為研究場域，有效問卷回收率為63.88%。本研究結果顯示，整體而言，大學數位原住民在學習方式面向屬於中度的感覺型；學習感官面向偏向中度之視覺型；學習態度面向微偏反思型；學習思考模式面向微偏循序型。本研究亦發現，在性別、年級和領域（學院）上，學習風格分布狀態各有特色、複雜多元。最後，建議教師依據學習風格調整教學，適性地引導大學數位原住民進行有效學習。 “The learner-basis and adaptive teaching and learning” is of great urgency in the digital age. The fundamental of adaptive teaching and learning is to understand students learning styles. Thus this paper aims to explore the distributions and degrees of college students’ learning styles. The research surveyed college students coming from one private university in Taipei and received the return rate of 63.88%. This research found that, all of these digital natives in college tend to have moderate sensory perception and moderate visual learning but also attempt to have reflective learning attitude and sequential thinking slightly. The research also found that there are different distribution of learning styles in gender, age, and discipline (colleges). This paper implies that the more adaptive instruction can respond to individual learning styles, the better learning effectiveness of the college digital natives can be.